The religious estates of the Beaterio del Santissimo Rosario de Molo in Iloilo City, 1925-1969. - Tirol, Jose Mari Benjamin F. U.
The study seeks to determine the historical development of the religious estates of the Beaterio del Santissimo Rosario de Molo, a religious congregation of Dominican sisters based in Molo City. The history of the Congregation cannot be separated from the history of its estates, because it was their acquisition of these estates that brought them to Iloilo City in the first place., The study constructs the history of the Congregation from its establishment in 1925 until 1969, when the Hacienda Alipion case was finally adjudicated. Within this period, the study seeks to determine the location of the Congregation's estates in Iloilo City, as well as determine the source/s of these estates. Also of importance is the reasons why the Beaterio came to own these estates. Controversial issues arising out of their ownership of these estates (like the Hacienda Alipion case) were also examined. There is also a description of their role in the community, as brought about by their estate ownership. The study utilizes library research in constructing a background about estates in general, which as a phenomenon, originated during the Spanish period. With regards the Beaterio estates, data from the City Registry of Deeds and the City Assessors' Office are used, along with interviews with knowledgeable members of the Congregation. The study found out that the estates were donated by Don Ignacio Aroyo, a local patron, since his daughter, Mother Rosario, was a member of the order. The estates he donated are spread over the different barangays of the Iloilo City districts of Arevalo, Molo, and City Proper. The other estates he donated can be found in Oton, Zarraga in Iloilo, and La Castellana and Hinigaran in Negros Occidental. The study also found out that the Sisters, unlike the religious orders of the past, did not actively express their desire of becoming estate owners. It was Don Ignacio's daughter Mother Rosario who was the reason why her father donated the estates. In fact, it was his donation which led to the establishment of a Dominican congregation in Iloilo. Two issues arose out of the Sisters' ownership of the estates, and both of these were caused by the other heirs of Don Ignacio, specifically his daughter-in-law Dona Jesusa and her children. First, they sought to have a share in Mother Rosario's inheritance from her father, which she bequeathed to the Beaterio. In the ensuing court case, the Beaterio won. The next issue arose out of the Beaterio's ownership of Hacienda Alipion. The Arroyos contended that the Beaterio did not own this land, which was part of Don Ignacio's donation, because it was not Don Ignacio's in the first place. This time the Arroyos won the case, resulting in their ownerhip of the contested lot. Education is the Congregation's vocation, and it is through education that it is able to play a role in the community. Although it operates only one school in Iloilo City, it is in charge of many others outside the city, as well as six others in Mindanao, and six others abroad. Religious estates then and now have not changed much with regards their origins but in terms of their purposes and the ways they are utilized by their owners, much has changed.